What Ontario MAID Death Review Committee Reports Tell Us About Canada’s MAID Policy and Practice — And About the Overhaul It Needs - Lemmens, Trudo (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2025)
This paper critically examines the evidence of Medical Assistance in Dying (MAID) practice in Ontario, as documented in reports from the Ontario Chief Coroner’s MAID Death Review Committee (MDRC), of which the author is a member. Drawing on case narratives and anonymized discussions summarized in a recent MDRC report on dementia, and in earlier MDRC reports, the author highlights troubling components of current MAID practice, particularly focusing on MAID of persons with dementia. The paper documents at times minimalistic capacity evaluations, questionable informed consent procedures, and flexible interpretations of legal criteria such as “reasonably foreseeable natural death” and “advanced state of irreversible decline.” The analysis reveals how current practices may circumvent criminal law-based legislative safeguards, including through the use of Waivers of Final Consent that resemble advance requests for MAID, which are prohibited under the Criminal Code. The paper argues that guidance documents of the Canadian Association of MAID Assessors and Providers contribute to practices that appear in tension with the law. In conclusion, the paper calls for an overhaul of the system, including through stricter legislative criteria, independent review mechanisms, and enhanced professional oversight, which should reflect the irreversible and most serious outcome of the procedure.